Deformation of phospholipid vesicles in an optical stretcher - Delabre, Ulysse; Feld, Kasper; Crespo, Eleonore; Whyte, Graeme; Sykes, Cecile; Seifert, Udo; Guck, Jochen (Soft Matter, 2015)
Phospholipid vesicles are common model systems for cell membranes. Important aspects of the membrane function relate to its mechanical properties. Here we have investigated the deformation behaviour of phospholipid vesicles in a dual-beam laser trap, also called an optical stretcher. This study explicitly makes use of the inherent heating present in such traps to investigate the dependence of vesicle deformation on temperature. By using lasers with different wavelengths, optically induced mechanical stresses and temperature increase can be tuned fairly independently with a single setup. The phase transition temperature of vesicles can be clearly identified by an increase in deformation. In the case of no heating effects, a minimal model for drop deformation in an optical stretcher and a more specific model for vesicle deformation that takes explicitly into account the angular dependence of the optical stress are presented to account for the experimental results. Elastic constants are extracted from the fitting procedures, which agree with literature data. This study demonstrates the utility of optical stretching, which is easily combined with microfluidic delivery, for the future serial, high-throughput study of the mechanical and thermodynamic properties of phospholipid vesicles.
CRIS-Team Scopus Importer:2022-08-05